2009
DOI: 10.1002/art.24342
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic assessment of age‐related knee joint space changes in women: A 4‐year longitudinal study

Abstract: Objective. To analyze a population-based cohort of women in order to establish normal values of joint space width (JSW) and to evaluate the existence of age-related joint space loss (JSL). Methods. Knee radiographs were performed 4 years apart in women from the OFELY (Os des Femmes de Lyon) Cohort. Posteroanterior radiographs of both knees were taken in semiflexion with a standardized fluoroscopically assisted protocol. Radiographs were qualitatively evaluated using a scoring system based on the Altman score t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 36 publications
2
30
0
1
Order By: Relevance
“…They found that lateral compartment BMLs sustained after ACL rupture, completely resolved after 2 years in almost all patients but 34 % patients developed new BMLs over the 2-year follow-up period. In our study, there were no significant differences in the lateral compartment between the injured and the noninjured groups in both cohorts but we did see an approximate doubling of prevalence in the medial compartment, a site which is of greater relevance to OA in older adults [33]. Data from this study suggests that age may not play a major role in the association between knee injury and BMLs as we saw very similar trends in both cohorts at all sites.…”
Section: Discussionsupporting
confidence: 63%
“…They found that lateral compartment BMLs sustained after ACL rupture, completely resolved after 2 years in almost all patients but 34 % patients developed new BMLs over the 2-year follow-up period. In our study, there were no significant differences in the lateral compartment between the injured and the noninjured groups in both cohorts but we did see an approximate doubling of prevalence in the medial compartment, a site which is of greater relevance to OA in older adults [33]. Data from this study suggests that age may not play a major role in the association between knee injury and BMLs as we saw very similar trends in both cohorts at all sites.…”
Section: Discussionsupporting
confidence: 63%
“…In addition, the chance of requiring TKA increased 13% for every year of age. Older age is the strongest predictor of radiographic joint space narrowing and the development of knee OA [35,39]. In this study, age is also a strong predictor of TKA use once symptomatic end-stage knee OA has developed, with younger persons less likely to undergo TKA.…”
Section: Discussionmentioning
confidence: 73%
“…Two-thirds of individuals with isolated ACL injury seem to have good long-term radiographic outcome, suggesting our focus should not only be on ACL injury prevention programs 52 , but also secondary injury prevention programs after ACLR. Very few studies have prospectively evaluated aged-related changes in OA 12 , but studies have shown significant decrease in joint space width (JSW) with older age 16 . In the uninjured contralateral knee in the current study, the rate of radiographic TF OA increased from 4% to 13% over the 5 years follow-up (Table 3a), indicating also a significant deterioration over time for the uninjured knee.…”
Section: Discussionmentioning
confidence: 99%